2008
DOI: 10.1016/j.medengphy.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Biodex system 3 pro computerized dynamometer in passive mode

Abstract: A specific experimental design has been developed to determine the accuracy of the Biodex system 3 pro dynamometer in passive mode. Five cyclic stretching repetitions were imposed to an elastic rubber band at different velocities using the dynamometer, and the torque produced was measured using both the dynamometer and external force and position sensors. Velocity patterns performed by the dynamometer were also characterized and our results show that these patterns were reliable (ICC = 1.00). The torque measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
5
16
0
8
Order By: Relevance
“…The dynamometer also measured the ankle angle (y), the joint angular velocity (o) and the passive torque (T) produced by the ankle joint in resistance to passive motion in reliable and valid ways (Nordez et al, 2008a). Subjects were required to lie on the dynamometer and extend their right leg fully (Nordez et al, 2008c).…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamometer also measured the ankle angle (y), the joint angular velocity (o) and the passive torque (T) produced by the ankle joint in resistance to passive motion in reliable and valid ways (Nordez et al, 2008a). Subjects were required to lie on the dynamometer and extend their right leg fully (Nordez et al, 2008c).…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…In addition, a recent study has shown that, because of acceleration capacities of the Biodex system, the angular velocity is not constant for high preset velocities (Nordez et al, 2008a). Therefore, equations of the rheological model were solved numerically using Simulink s (The Mathworks, Natick, USA) and the ODE45 solver in which 0 was considered the initial condition for T 3 .…”
Section: Article In Pressmentioning
confidence: 99%
“…However, before the isokinetic dynamometer can be used for research or clinical rehabilitation, its reliability must be tested 9 . Reliability is defined as the consistency between different measures performed under similar conditions 10 , and it shows the degree to which test scores are free from errors of measurement 11 . Therefore, when the test is reliable, device, clinician or testing errors can be excluded 9 and measures obtained during isokinetic evaluation over a period of time can be compared 9,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, previous studies used the passive mode for subjects with muscle weakness, such as children with cerebral palsy 21 and patients with neuromuscular disorders 22 . In the passive mode test, the individual performs a maximal effort and, at the same time, the dynamometer produces movement at a constant preset velocity 10 . Therefore this test is called an active-assisted test.…”
Section: Introductionmentioning
confidence: 99%
“…De nombreuses études ont utilisé ce type de dynamomètre pour mobiliser passivement une articulation tout en mesurant la résistance à l'étirement du SMA [7][8][9]11,12] et à différentes vitesses [13][14][15][16][17][18][19]. L'utilisation de ces dynamomètres isocinétiques pour l'exploration passive du SMA a nécessité d'étudier la sensibilité et la validité des mesures [12].…”
Section: Méthodes De Caractérisation Du Comportement Mécanique Du Smaunclassified